Microscopic biasing of discrete-time quantum trajectories. (9th August 2021) - Cilluffo, Dario; Buonaiuto, Giuseppe; Lesanovsky, Igor; Carollo, Angelo; Lorenzo, Salvatore; Palma, G Massimo; Ciccarello, Francesco; Carollo, Federico
Abstract: We develop a microscopic theory for biasing the quantum trajectories of an open quantum system, which renders rare trajectories typical. To this end we consider a discrete-time quantum dynamics, where the open system collides sequentially with qubit probes which are then measured. A theoretical framework is built in terms of thermodynamic functionals in order to characterize its quantum trajectories (each embodied by a sequence of measurement outcomes). We show that the desired biasing is achieved by suitably modifying the Kraus operators describing the discrete open system dynamics. From a microscopical viewpoint and for short collision times, this corresponds to adding extra collisions which enforce the system to follow a desired rare trajectory. The above extends the theory of biased quantum trajectories from Lindblad-like dynamics to sequences of arbitrary dynamical maps, providing at once a transparent physical interpretation.